2011
DOI: 10.2489/jswc.66.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Financial and environmental consequences of a voluntary farm environmental assurance program in Michigan

Abstract: Abstract:The Michigan Agriculture Environmental Assurance Program is a voluntary environmental management program for Michigan farms. The Michigan Agriculture Environmental Assurance Program encourages farm managers to become better environmental stewards through writing Comprehensive Nutrient Management Plans and incorporating changes to comply with regulations as well as generally accepted management practices and recommendations. Early-adopting livestock producers with verified operations were interviewed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…MAEAP does not involve adoption of changed practices to benefit the environment; instead, it is designed to reduce farmers’ legal and environmental risks by education, farm‐specific risk assessment and on‐site verification of `generally accepted agricultural practices’. A previous study on early‐adopting livestock producers found the primary motivation to participate in MAEAP was concern about existing or potential environmental regulations, rather than a predisposition toward environmental stewardship (Vollmer‐Sanders et al. , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…MAEAP does not involve adoption of changed practices to benefit the environment; instead, it is designed to reduce farmers’ legal and environmental risks by education, farm‐specific risk assessment and on‐site verification of `generally accepted agricultural practices’. A previous study on early‐adopting livestock producers found the primary motivation to participate in MAEAP was concern about existing or potential environmental regulations, rather than a predisposition toward environmental stewardship (Vollmer‐Sanders et al. , 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Farmers' decisions are shaped by personal opinions, such as preferences over conservation measures, beliefs about the programme and degrees of risk aversion 21,31 . Factors such as income levels, asset ownership, age, and access to other economic opportunities also correlate with the decision to adopt, as they affect the capacity of the target population to reap benefits from the progra mme [5][6][7]12,29,[32][33][34] . The decision to adopt is also affected by the biophysical characteristics of the land plot, and the institutional and policy context.…”
Section: Discussionmentioning
confidence: 99%
“…It is administered by the Michigan Department of Agriculture and Rural Development in consultation with an advisory council, but it was established by a coalition of farmers, commodity groups, state and federal agencies, and environmental conservation groups. The primary motivation for producers to gain MAEAP certification is to mitigate risk from existing and potential environmental regulations, and additional sources of motivation are good stewardship and technical assistance in managing nutrients (Vollmer-Sanders et al 2011). Other states have similar programs; one example is New York's Agricultural Environmental Management program (NYSDAM 2013).…”
Section: Pressure From Outside the Supply Chainmentioning
confidence: 99%